2017
DOI: 10.1177/1534735416686687
|View full text |Cite
|
Sign up to set email alerts
|

Bone Mineral Density, Balance Performance, Balance Self-Efficacy, and Falls in Breast Cancer Survivors With and Without Qigong Training: An Observational Study

Abstract: Purpose: A deterioration in bone strength and balance performance after breast cancer treatment can result in injurious falls. Therefore, interventions need to be developed to improve the bone strength and balance ability of breast cancer survivors. This cross-sectional exploratory study aimed to compare the bone mineral density (BMD), balance performance, balance self-efficacy, and number of falls between breast cancer survivors who practiced qigong, breast cancer survivors who did not practice qigong, and he… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
23
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(24 citation statements)
references
References 25 publications
0
23
0
1
Order By: Relevance
“…In our study, worse results of balance tests were noted in the BG group with both closed and open eyes. Research by Fong et al has shown that properly selected exercise can improve balance in women after breast amputation [ 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…In our study, worse results of balance tests were noted in the BG group with both closed and open eyes. Research by Fong et al has shown that properly selected exercise can improve balance in women after breast amputation [ 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…44 A nivel psicosocial, mejora la percepción corporal, el control motor y equilibrio al realizar movimientos corporales. 45 A nivel social, el ejercicio es ampliamente aceptado y genera realimentaciones sociales positivas en los demás, lo que hace que la paciente se sienta corporalmente más atractiva. 46 La práctica del ejercicio ligero, como la caminata de 20 a 40 minutos algunas veces por semana, se ha asociado consistentemente a una pequeña reducción de síntomas depresivos en población sana 47 y con diversos tipos de cáncer; 48 sin embargo, en pacientes con CaMa, se ha reportado una mejoría estadísticamente no significativa (DEM: -0.15; IC95%: -0.30, 0.01).…”
Section: Ejerciciounclassified
“…Specific measurements are required to evaluate balance, strength, and endurance in the older population. Handgrip strength, knee isometric strength, sit-to-stand test (to measure lower body strength, balance, and range of motion), 4 m timed normal and brisk walk tests (to measure locomotion), 2 min walk test (to measure endurance), and timed one leg stance (to measure balance) are all parts of the recommended measurements for OSO syndrome [2,[60][61][62]. These tests are valuable measurements to assess fall risk and evaluate changes or deficits in body composition preceding OSO syndrome.…”
Section: Physical and Functional Performance Tests To Evaluate Oso Symentioning
confidence: 99%